Insights into Socio-Technical Transitions Towards Patterns of Sustainable Consumption in Water and Energy in South-American Mining - Two Argentinean Controversies [Visiones Sobre Los Tránsitos Socio-Técnicos Hacia Patrones de Consumo Sustentable en Agua y Energía en la Minería Sudamericana - Dos Controversias Argentinas] - Estenssoro-Saavedra, J; Parker-Gumucio, C; Baigorrotegui-Baigorrotegui, G (Instituto de Filosofia e Ciencias Humanas-UFRGS, 2014)
This paper addresses the problem of water and energy consumption in the South American mining from a perspective not much explored: the sustainable consumption. From the point of view of sociology and the social studies of science and technology, we expose the issue by presenting three different consumption patterns: conventional, alternative and progressive. Based on both secondary sources and semi-structured interviews, we looked into the controversies surrounding two Argentine historical mining projects: Cerro Vanguardia and La Alumbrera, by focusing our questions around sustainable consumption of resources such as water and energy. We noted the perceived urgency to move towards sustainable consumption patterns, as well as whom are those called to make it happen and what details would be needed at different scales to make the transition. Taking into account that water and energy are fundamental factors for the transition towards sustainable consumption patterns in mining, we propose that they are central to the management of local conflicts in Latin American environmental governance. This study is part of a larger research that encompasses several South American countries.